Դպրությունը Կիլիկյան Հայաստանի Սև լեռան հայկական վանքերում - Շիրինյան, Էռնա Մանեա («Նաիրի» հրատ.)
Having been in the same lore with the literature of Armenia nevertheless Cilician Armenian literature differed from it due to many natural reasons, among which the most important one seems to be a different environment and neighborhood. In this context a significant role played Cilician monasteries of Black Mountain. The existence of these monasteries is testified from the 5th -6 th centuries but there is no much information about activity of these monasteries at that time. Opposite to this, starting from the 11th century one can speak about the most flourishing and one can say ‗international‘ period for the activities at the Black Mountain‘s monasteries. It is even possible to evaluate them as an international center of teaching and learning for Greek, Syrian, Latin, Armenian and Georgian monks, ascetics and simply authors, who came in search of a spiritual guide.
Keywords: Կրթօջախ; Կիլիկյան Հայաստան